(untitled) (ItalianoLinguadue, 2019)
The Recreational Linguistics (Ludolinguistica) is a discipline which stimulates language learning through word games and lexical combinations. The pedagogical approach, created by da Anthony Mollica, is a “non-traditional” method to acquire linguistic and cultural skills. The method includes acrostics, mesostichs, tongue twisters, crossword puzzles, word searches, riddles, which Mollica advocates to teach language (vocabulary and grammar) as well as culture. “Motivate, amuse, teach” are the keywords suggested for ludolinguistica, a term which Nicola Zingarelli includes in his Vocabolario della lingua italiana in l998. The various pedagogical suggestions are aimed at providing a motivational tool in a relaxing environment for students learning another language or reinforcing the structures of their mother tongue. La Ludolinguistica: un metodo pedagogico creatro da Anthony Mollica per motivare gli astudenti ad apprendere la lingua La Ludolinguistica (Recreational Linguistics) è una disciplina che stimola l’apprendimento delle lingue attraverso giochi di parole e combinazioni lessicali. L’approccio pedagogico, creato da Anthony Mollica, è un metodo “non tradizionale” per acquisire competenze linguistiche e culturali. Il metodo include acrostici, mesostici, scioglilingua, cruciverba, ricerche di parole, indovinelli, che Mollica propone per insegnare la lingua (vocabolario e grammatica) e cultura. “Motivare, divertire, insegnare” sono le parole chiave della ludolinguistica, termine che Nicola Zingarelli inserisce nel suo vocabolario della lingua italiana nel 1998. I vari suggerimenti pedagogici sono volti a fornire uno strumento motivazionale in un ambiente rilassante per gli studenti che imparano un’altra lingua o rafforzano le strutture della loro lingua madre.